METHODOLOGY FOR THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS - Joldasov Ikhtiyor Suyundikovich (Western European Studies, 2024)
In this article, professional competence, professional self-awareness, ways of developing professional competence, methods and respect for professional values and orientation to the profession - this is the professional formation of the growing young generation, birth is a generalizing concept that is one of the components of universal culture, which is manifested in the example of support and development of human ability. The formation of professional competences of future teachers is to ensure that they act successfully on the basis of practical experience and knowledge in solving professional issues
Keywords: Professional competence; self-awareness; innate ability; selection